The Use of Digital Storytelling (DST) to Help Students in Learning Multimodal Writing - Dewi Puspitasari (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2018)
This article explores the use of DST and the explicit teaching in one of universities in Indonesia on how stu-dents use it to help the learning process. Using a digital story to teach English and Based on multimodal theory, the term of DST has been increasingly used by scholars to illustrate various forms of support of learn-ing to help students learn successfully in a classroom. Despite being widely used in educational context of many countries, DST has received scanty attention from teacher especially in ESP classes. This article specif-ically describes our experience of using DST as a learning aid with students of 18 to 19 years old. In this project they individually created collected the photographs based on their interest related to the specified theme as multimodal text. In the process they utilized two linguistic resources (Bahasa Indonesia and Eng-lish) to help them in understanding the process of creation. Several supports from machine translation and machine pronunciation software were employed during the creation of DST project. The result shows that DST helps students in composing narrative writing by analyzing the visual prompts. This proves that DST is impending to support the writing process as students were engaged during the process.